Linking Bibliographic Retrieval to Clinical Reports: PsychTopix - Powsner, Seth M. (1989)
PsychTopix is an expert system which guides the clinician from a computer-based clinical record to a focused bibliographic retrieval. Specifically, PsychTopix searches the literature for references pertinent to a psychiatric consultation report. It provides intelligent guidance by drawing on a knowledge base of current issues in psychiatry. It scans the report to determine which clinical topics (issues) are likely to be relevant to the case. The clinician then selects those topics for which he or she desires a literature search. There is no need for the user to know the mechanics or protocols of computerized literature retrieval. PsychTopix initiates a Medline search and presents the references retrieved to the user. More generally, PsychTopix provides an effective demonstration of the key topics approach to medical database linkage.